Innovación Organizacional en la Estrategia de Internacionalización en Pymes Vitivinícolas: El Caso Chileno - Argandona-Gomez, F (UNIV SANTIAGO DE CHILE, 2024)
This investigation aims to determine the components of the organizational innovation in Chilean bottled wine SMEs, to strengthen the internationalization strategy in global markets, concerning the leading countries with international recognition. These results should help enhance competitiveness in cosmopolitan markets with wine tradition. In operational terms, it includes five stages: data collection from wine SMEs, instrument design (questionnaire), application of this instrument in companies through personalized field work, processing, analysis, and systematization of the collected data through office automation instruments- mainly the SPSS statistical program for a validation-and delivery of these results to each of the participant companies. As one of the primary outcomes, wine SMEs are gaining legitimacy through organization innovation as a corporate strategy to have opportunities to stay in national and international markets.